2013
DOI: 10.1186/1471-2407-13-436
|View full text |Cite
|
Sign up to set email alerts
|

The presence of tumour-associated lymphocytes confers a good prognosis in pancreatic ductal adenocarcinoma: an immunohistochemical study of tissue microarrays

Abstract: BackgroundTumour-associated lymphocytes (TALs) have been linked with good prognosis in several solid tumours. This study aimed to evaluate the prognostic significance of CD3, CD8 and CD20 positive lymphocytes in pancreatic ductal adenocarcinoma.MethodsAfter histological re-evaluation of the tumours of 81 patients who underwent surgical resection for exclusively pancreatic ductal adenocarcinoma, tissue micro-arrays (TMA) were constructed and immunohistochemistry was performed for CD3, CD8 and CD20. The number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 32 publications
4
67
0
Order By: Relevance
“…12 Tewari et al evaluated the prognostic significance of CD3+, CD8+, and CD20+ TILs in 81 PDAC patients and found an association between high levels of CD3+ and CD20+ TILs and higher survival rates. 31 In another study, Ino et al found that patients with a high CD4+ T-cell count, high CD8+ T-cell count, and low Treg count (defined as values higher and lower than the median for tumor-infiltrating immune cells) had longer survival than those with a low CD4+ T-cell count, low CD8+ T-cell count, and high Treg count. 32 A growing body of evidence suggests that the TIL status in the residual tumor after neoadjuvant chemotherapy can predict clinical outcomes of breast cancer patients.…”
Section: Discussionmentioning
confidence: 97%
“…12 Tewari et al evaluated the prognostic significance of CD3+, CD8+, and CD20+ TILs in 81 PDAC patients and found an association between high levels of CD3+ and CD20+ TILs and higher survival rates. 31 In another study, Ino et al found that patients with a high CD4+ T-cell count, high CD8+ T-cell count, and low Treg count (defined as values higher and lower than the median for tumor-infiltrating immune cells) had longer survival than those with a low CD4+ T-cell count, low CD8+ T-cell count, and high Treg count. 32 A growing body of evidence suggests that the TIL status in the residual tumor after neoadjuvant chemotherapy can predict clinical outcomes of breast cancer patients.…”
Section: Discussionmentioning
confidence: 97%
“…Improved prognosis was seen with high levels of infiltration by CD3 + , CD8 + or CD4 + T cells and CD20 + B cells [113115]. Further histological characterization of the proposed immunogenic subtype of pancreatic ductal adenocarcinoma will be of value to inform forthcoming immunotherapy clinical trials.…”
Section: Tils In Upper Gastrointestinal Tract Carcinomasmentioning
confidence: 99%
“…Not only is there increasing clinical evidence that infiltration of immune cells into the tumor is prognostically significant [136][137][138], but the avoidance of immune destruction is considered an emerging hallmark of cancer [139]. Current opinions suggest that there are at least two ways in which the immune system is involved in cancer.…”
Section: Regulatory Immune Cellsmentioning
confidence: 99%